Association between Axial Length to Corneal Curvature Radius Ratio and Myopia in Adult Patients - Yanyun Fan; Yikeng Huang; Xionggao Huang (Journal of Ophthalmology)
Purpose. To analyze the distribution characteristics of axial length to corneal curvature radius ratio (AL/CR) and other ocular biometric parameters in adult myopia patients and their association with myopia. Methods. A cross-sectional study was conducted among patients with no eye diseases except ametropia who attended the optometry clinic of the First Affiliated Hospital of Hainan Medical College from January 2022 to June 2022. In total, 187 eyes (right eye) of 187 myopic patients aged 18–35 years were selected by random sampling. Based on the results of spherical equivalent (SE, (D)) obtained by postdilation optometry, all subjects were divided into three groups: mild myopia (≤−0.50D and >−3.00D, 42 eyes), moderate myopia (≤−3.00D and >−6.00D, 80 eyes), and high myopia (≤−6.00D, 65 eyes). The axial length (AL), corneal curvature radius (CR), and AL/CR were measured and compared between the three groups. The association between AL and AL/CR of the eye and SE was analyzed by multiple linear regression. Also, the predictive ability of AL/CR for high myopia was investigated by ROC curve. Results. There were no statistically significant differences in age, gender, or intraocular pressure between the three groups. The mean values of AL/CR in mild, moderate, and high myopia groups were 3.17 ± 0.06, 3.31 ± 0.08, and 3.43 ± 0.10, respectively, and the difference between the groups was statistically significant P<0.001). Linear regression analysis showed that both AL and AL/CR were strongly negatively correlated with SE (P<0.05), while CR had a weak positive correlation with SE without statistically significant differences (P>0.05). The adjusted linear regression equation shows that for every 0.1 unit increase in AL/CR, SE increases by 1.54 D. Compared with 0.830 (95% confidence interval: 0.769 to 0.900) for AL, the area under ROC curve of AL/CR was 0.896 (95% confidence interval: 0.851 to 0.941), indicating that the diagnostic value of AL/CR for high myopia was higher than that of AL (P< 0.01). When the Youden index reached its maximum (0.626), the AL/CR cutoff point was 3.309, and the sensitivity and specificity were 0.954 and 0.672, respectively. Conclusion. This study showed that AL and AL/CR in adult myopia patients were significantly negatively correlated with SE, and the corralation between AL/CR and SE is greater than that between AL and SE. Therefore, AL/CR can be used to analyze the dynamic changes of SE in the development of adult myopia independently of optometry on a certain basis, and it is especially suitable for the diagnosis of high myopia in adults. This trial is registered with ChiCTR2300069070.